Downregulation of PI3K/AKT/mTOR Pathway in Juglone-Treated Bovine Oocytes - Marwa El-Sheikh; Ayman Mesalam; Atif Ali Khan Khalil; Muhammad Idrees; Mi-Jeong Ahn; Ahmed Atef Mesalam; Il-Keun Kong (MDPI AG, 2023)
We have previously reported that juglone, a natural compound found in Juglandaceae with a wide range of biological activities, can reduces the developmental competence of bovine oocytes. In the current study, we investigated the possible mechanisms behind the toxicity of juglone and the relationship with PI3K/AKT/mTOR signaling during the in vitro maturation (IVM) of oocytes. Results show that oocyte exposure to juglone was associated with a significant decrease in filamentous actin (F-actin) accumulation. The RT-qPCR showed downregulation of the meiosis progression indicator GSK-3A, oocyte development marker BMP15, mitochondria fusion controlling MFN1, oxidative stress-related OGG1, and histone methylation-related EZH1, EZH2, SUZ12, G9a, and SUV39H2 genes in juglone-treated oocytes. In addition, glycolysis- (PFK1 and GLUT1), ATP synthesis- (ATPase8 and ATP5F1B), and OXPHOS-specific markers (SDHA and SDHD), as well as the oocyte survival regulators (SOD2, VEGF, and MAPK1) significantly decreased upon juglone treatment. Moreover, lower expression of PI3K, AKT, and mTOR was observed at the transcriptional and/or translational level(s). The autophagy markers LC3B and beclin-1 as well as the DNA damage-specific marker 8-OxoG displayed overexpression in juglone-exposed oocytes. Taken together, our results show that administration of juglone during the IVM can reduce the quality and developmental health of bovine oocytes through downregulation of the PI3K/AKT/mTOR pathway and its downstream signaling cascades.